2015
DOI: 10.3732/ajb.1400254
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking refugia: Tree topology, divergence dates, and demographic history trace the distribution of the endangered Plymouth gentian (Sabatia kennedyana) from the Pleistocene glaciation to present day

Abstract: • Premise of study: Molecular population genetics is a powerful tool to infer how species responded to past environmental change. In the northern hemisphere, interest is increasing in how species responded to changes in ice coverage and temperature during the last glaciation maximum (LGM, between 18000–21000 yr ago) with a common assumption that glacial refugia were located at the southern edge of a species range.• Methods: We reconstructed the glacial and postglacial phylogeography of Sabatia kennedyana, a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…However, other species with similarly wide ranges have been found to lack such spatial patterns in genetic diversity, suggesting that postglacial range expansion occurred gradually along an expansive migration front (e.g., Lumibao et al., 2017; Bemmels and Dick, 2018). To complicate matters, some species are hypothesized to have survived the LGM in ice‐free, coastal areas well above the southern extent of the ice sheets (e.g., Godbout et al., 2010; Suarez‐Gonzalez et al., 2015). Taken together, these findings demonstrate that the biogeographic history of ENA has been complicated, and that the recovery of a common phylogeographic pattern for the postglacial history of ENA forest species is unlikely.…”
mentioning
confidence: 99%
“…However, other species with similarly wide ranges have been found to lack such spatial patterns in genetic diversity, suggesting that postglacial range expansion occurred gradually along an expansive migration front (e.g., Lumibao et al., 2017; Bemmels and Dick, 2018). To complicate matters, some species are hypothesized to have survived the LGM in ice‐free, coastal areas well above the southern extent of the ice sheets (e.g., Godbout et al., 2010; Suarez‐Gonzalez et al., 2015). Taken together, these findings demonstrate that the biogeographic history of ENA has been complicated, and that the recovery of a common phylogeographic pattern for the postglacial history of ENA forest species is unlikely.…”
mentioning
confidence: 99%
“…Subsequently, environment variables whose correlation is greater than 0.8 and less than −0.8 were removed in order to avoid the over-fitting phenomenon caused by the high correlation of environment variables. Combined with the variables whose correlation values are much larger than the mean value, the following eight variables (bio2, 3,4,9,10,11,12,15) are finally obtained.…”
Section: Species Distribution Modelingmentioning
confidence: 99%
“…During the Quaternary periods, the global climate experienced repeated cycles of glacial and interglacial stages [1], which lead to the changes of geographic distributions and genetic structures of most organisms [2]. Some studies revealed that most plant species survived in the glacial refugia under the unfavorable Pleistocene glacial conditions and became the sources of post-glacial recolonization processes, which has been generally accepted in biogeography [3,4]. In addition, it is generally assumed that the isolations between biological refugees lead to the formation of new species or subspecies, especially those with a weak migratory capacity [5].…”
Section: Introductionmentioning
confidence: 99%
“…Th ese include the frequent location of glacial refugia in the southern reaches of the Northern Hemisphere, with refugia found in the southern peninsulas of Europe and along the Gulf Coast in the eastern United States ( Taberlet et al, 1998 ;Avise, 2000 ;Hewitt, 2000 ;Soltis et al, 2006 ). Th ere is also now general acceptance of additional "cryptic" refugia, where species survived close to the ice sheet, both in Europe and North America ( Stewart and Lister, 2001 ;Tribsch and Schonswetter, 2003 ;McLachlan et al, 2005 ;Provan and Bennett, 2008 ;Parducci et al, 2012 ;Suarez-Gonzalez et al, 2015 ). In Europe, distinct species exhibit congruence with respect to the locations of glacial refugia, subsequent colonization routes, and areas of secondary contact ( Taberlet et al, 1998 ;Hewitt, 2000 ).…”
mentioning
confidence: 96%